Targeting cancer cells with nanotherapeutics and nanodiagnostics: Current status and future perspectives. (February 2021) - Ali, Eunus S.; Sharker, Shazid Md.; Islam, Muhammad Torequl; Khan, Ishaq N.; Shaw, Subrata; Rahman, Md. Atiqur; Uddin, Shaikh Jamal; Shill, Manik Chandra; Rehman, Shahnawaz; Das, Niranjan; Ahmad, Saheem; Shilpi, Jamil A.; et al.
Abstract: Nanotechnology is reshaping health care strategies and is expected to exert a tremendous impact in the coming years offering better healthcare facilities. It has led to not only therapeutic drug delivery feasibility but also to diagnostics. Materials in the size of nano range (1–100 nm) used in the design, fabrication, regulation, and application of therapeutic drugs or devices are classified as medical nanotechnology and nanopharmacology. Delivery of more complex molecules to the specific site of action as well as gene therapy has pushed forward the nanoparticle-based drug delivery to its maximum. Areas that benefit from nano-based drug delivery systems are cancer, diabetes, infectious diseases, neurodegenerative diseases, blood disorders and orthopedic-related ailments. Moreover, development of nanotherapeutics with multi-functionalities has a considerable potential to fill the gaps that exist in the present therapeutic domain. In cancer treatment, nanomedicines have superiority over current therapeutic practices as they can effectively deliver the drug to the affected tissues, thus reducing drug toxicities. Along this line, polymeric conjugates of asparaginase and polymeric micelles of paclitaxel have recently been recommended for the treatment of various types of cancers. Nanotechnology-based therapeutics and diagnostics provide greater effectiveness with less or no toxicity concerns. Similarly, diagnostic imaging holds promising future applications with newer nano-level imaging elements. Advancements in nanotechnology have emerged to a newer direction which use nanorobotics for various applications in healthcare. Accordingly, this review comprehensively highlights the potentialities of various nanocarriers and nanomedicines for multifaceted applications in diagnostics and drug delivery, especially the potentialities of polymeric nanoparticle, nanoemulsion, solid-lipid nanoparticle, nanostructured lipid carrier, self-micellizing anticancer lipids, dendrimer, nanocapsule and nanosponge-based therapeutic approaches in the field of cancer. Furthermore, this article summarizes the most recent literature pertaining to the use of nano-technology in the field of medicine, particularly in treating cancer patients.